Upaya Meningkatkan Kemampuan Sosial Anak melalui Bermain Peran di KB Al Hikmah Tajungsari Pati - Karmini, Karmini (Indonesian Journal of Islamic Early Childhood Education, 2017)
This study aims to determine whether role play can improve the social skills of children aged 4-5 years in Al Hikmah Tajungsari Tlogowungu Pati. This research is a Classroom Action Research. This research was conducted in first semester of academic year 2016/2017. This research will be carried out in 2 cycles, and each cycle aims to improve childrens social skills through main role. The analysis is done following the concept given by Miles and Hubberman, that is Reduction data, Display data and Conclusion Drawing / Verification. The results showed that the observation results of students social ability by using the role playing method of KB Al Hikmah Tajungsari Tlogowungu Pati. The students social skills are improved after attending the students ability development by applying role playing methods. In pre cycles of students social ability 24% in developed as espected (BSH) category. In the first cycle students social ability of 52% in the very good development (BSB) category. In the second cycle students social ability score of 80% or an increase of 28% compared to cycle I.